The relationship between quality of college life and academic hardiness among college students - Nindya Putri Aprodita (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
The purpose of this study is to explore the relationship between students’ quality of college life and their academic hardiness. The quantitative method was used in combination with a correlational approach. The measuring instrument used was an adaptation of QCL Measure by Sirgy (2007) and Academic Hardiness Scale by Benishek (2005). The population of the study was 105 students majoring in psychology at a private university in Jakarta, while the sample consisted of 89 students. The data were analyzed using Pearson correlation test to obtain the correlation coefficient between the two variables. The results of the study showed that the quality of college life has a significant relationship with students’ academic hardiness. It is suggested that education institutions enforce the quality of college life aspect that has the strongest relationship with academic hardiness, which is the academic aspect. The academic aspect encompasses the quality of lecturers, learning environments, and learning materials.